INCREASING STUDENTS’ VOCABULARY OF SEVENTH GRADE AT SMP N 1 GALANG THROUGH HANGMAN GAMES - Diyenti Rusdin (Universitas Madako Tolitoli, 2019)
The objective of the research is to prove whether the use of hangman games effective in increasing students’ . This pre-experimental study use 22 students as a sample. They are grade VIId of SMP N 1Galang . The procedure of this research consists of pretest, treatment, and posttest. The result It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 56.72 while in the post-test improved up to 90.64. The data of this research are analyzed by using SPSS Program version 16.0. Then the data of both tests are analyzed by using T-test, and the result shows that the T-test value 9.681 is high than T-table value 2.080. It can be inferred that hangman games is very effective to improve students’ vocabulary. Keywords: increasing , vocabulary, Hangman games